Correlates of avoidance help-seeking behaviors among Malaysian adolescents - Awang Hashim, Rosna; Hashim, Jahara; Yaakub, Noran Fauziah; Othman, Abu Hassan; Md Ali, Ruzlan (UUM College of Arts and Sciences, 2004)
The study examined correlates of avoidance help seeking behaviors among secondary school students in the state of Kedah, Malaysia. Particularly,the study examined the relationship between implicit beliefs about intelligence, academic goal orientations, perception of social and cognitive competence, classroom goal orientations, threat to self-worth, and avoidance help-seeking behavior in learning mathematics. Surveys were administered to 1849 secondary school students (1449 Malays and 400 non- Malays: 900 males and 949 females), aged between 13 and 17 years, who were studying mathematics. The instrument for the survey was adapted mainly from the Pattern of Adaptive Learning Scale (PALS). Descriptive statistics was used to examine patterns of avoidance help-seeking behavior:Pearson correlation was used to examine relationships among the variables. Findings indicated that students who perceived math ability as static and students who perceived peers and teachers as posing a threat to their self-worth are the least likely to ask for help. Students who learnt for mastery and who had a high perception of their math cognitive competence were least likely to avoid help seeking when needed. A stepwise regression analysis identified low task focused goals, high peer and teacher threats, low perception of cognitive competence, and a fixed belief about the nature of intelligence as the five main predictors of avoidance help-seeking behavior in learning mathematics. Discussion will center on these significant psychological factors that have implications for the teaching and learning of mathematics at the secondary school level.